Rational design and synthesis of a highly porous copper-based interpenetrated metal-organic framework for high CO2 and H2 adsorption - Bose, Purnandhu (2015)
Interpenetrated metal–organic frameworks (MOFs) are often observed to show lower porosity than their non-interpenetrating analogues. It would be highly desirable if the interpenetrated MOFs could still provide high stability, high rigidity, and optimal pore size for applications. In this work, an asymmetrical tricarboxylate organic linker was rationally designed for the construction of a copper(II)-based microporous MOF with a twofold interpenetrated structure of Pt3O4 topology. In spite of having structural interpenetration, the activated MOF shows high porosity with a Brunauer–Emmett–Teller surface area of 2297 m2g−1, and high CO2 (15.7 wt % at 273 K and 1 bar) and H2 uptake (1.64 wt % at 77 K and 1 bar).